Compensation as a Strategy in Teaching Reading to EFL Junior High School Students - Hartini A. Pasumbu; Yuliana Dg Macora (Sintuwu Maroso Journal of English Teaching, 2018)
This study aims to: 1) analyze the application of compensation strategy in teaching reading ; and 2) identify the students’ achievement level in reading using compensation strategy to the Eighth Grade students of SMP Negeri 1 Poso Pesisir. The research method is descriptive qualitative research. The data are the teacher and students’ interaction, and the students’ achievement. The samples are the Eighth Grade students SMP N 1 Poso Pesisir consist of 22 students. The qualitative data were obtained by doing observation and taking field notes. The result from the test evaluation, the students got good marks. It means that the students understood the text. They can answer their test correctly. In the time, the use of compensation strategies can help the students in guessing difficult words, so when the researchers gave them the test, they understood of how to answer it. Hence it can be concluded that compensation strategy through guessing intelligently is one of teaching aid that the students and the teacher need it in order to maintain interest and motivation, and increasing their understanding in reading descriptive text.Keywords: compensation, teaching reading, literacy practice, EFL junior highschool students